FRICTION ANALYSIS ON SCRATCH DEFORMATION MODES OF VISCO-ELASTIC-PLASTIC MATERIALS - Budi Setiyana; Imam Syafaat; Jamari Jamari; DikJoe Schipper (Dept. of Chemical Engineering, Diponegoro University, 2013)
Understanding of abrasion resistance and associated surfaces deformation mechanisms is of primary importance in materials engineering and design. Instrumented scratch testing has proven to be a useful tool for characterizing the abrasion resistance of materials. Using a conical indenter in a scratch test may result in different deformation modes, like as elastic deformation, ironing, ductile ploughing and cutting. This paper presents the friction analysis of some deformation modes of visco-elastic-plastic behaving polymer materials, especially PEEK (poly ether ether ketone).In general, it is accepted that the friction consist of an adhesion and a deformation component, which can be assumed to be independent to each others. During a scratch test, the friction coefficient is influenced by some parameters, such as the sharpness of indenter, the deformation modes and the degree of elastic recovery. Results show that the adhesion component strongly influences the friction in the elastic and ironing deformation mode (scratching with a blunt cone), friction for the cutting deformation mode (scratching with a sharp cone) is dominantly influenced by the deformation component. From the analysis, it can be concluded that the adhesion friction model is suitable for ironing - elastic deformation mode and the deformation friction model with elastic recovery is good for cutting mode. Moreover, the ductile ploughing mode is combination of the adhesion and plastic deformation friction model. ANALISIS FRIKSI PADA BENTUK DEFORMASI AKIBAT GORESAN PADA MATERIAL VISKO-ELASTIK-PLASTIK. Pemahaman tentang ketahanan abrasi dan deformasi permukaan yang menyertainya merupakan hal yang penting dalam rekayasa dan disain material. Peralatan uji gores terbukti ampuh untuk menyatakan ketahanan abrasi dari material. Pemakaian indenter kerucut dalam uji gores akan menghasilkan beberapa bentuk deformasi seperti halnya deformasi elastik, penyetrikaan, plowing dan pemotongan. Paper ini menyajikan analisis friksi dari beberapa bentuk deformasi permukaan dari material visko-elastik-plastik, khususnya pada PEEK (poly ether ether ketone). Secara umum dinyatakan bahwa friksi terdiri dari komponen adhesi dan deformasi yang diasumsikan tidak bergantung satu sama lain. Selama uji gores, koefisien friksi dipengaruhi oleh beberapa parameter, seperti ketajaman indenter, bentuk deformasi dan pemulihan elastik. Hasil menunjukkan bahwa komponen adhesi sangat berpengaruh pada deformasi elastic dan penyetrikaan (uji gores dengan indenter tumpul), sedang untuk pemotongan (uji gores dengan indenter tajam) sangat dipengaruhi oleh komponen deformasi. Dari analisis dapat disimpulkan bahwa model friksi adhesi cocok untuk deformasi elastic dan penyetrikaan, sedang model friksi deformasi dengan pemulihan elastic, cocok untuk pemotongan. Selain itu, plowing merupakan kombinasi dari model friksi adhesi dan deformasi.